Study Of The Attitude Of Students Of The Medical Faculty Of Gulistan State University To The Formation Of A Healthy Lifestyle (Texas Journal of Medical Science, 2024)
The article is devoted to the study of the attitude of students of the Medical Faculty of the Gulistan State University of the Republic of Uzbekistan to a healthy lifestyle and the study of factors influencing its formation. The object of the study were students of the Medical Faculty specializing in General Medicine, numbering 70 people.